2019
DOI: 10.1039/c9cc03921j
|View full text |Cite
|
Sign up to set email alerts
|

An effectivecis-β-octahedral Mn(iii) SALPN catalyst for the Mukaiyama–Isayama hydration of α,β-unsaturated esters

Abstract: Two cis-β-MnIIISALPN catalysts were synthesised and tested in the Mukaiyama–Isayama hydration of α,β-unsaturated esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Co(acac) 2 catalyzed oxygen mediated hydration failed to deliver the desired β‐hydroxy product. Of note, Rizzacasa and co‐workers previously demonstrated aerobic hydration of α,β‐unsaturated esters by using a designed Mn‐catalyst [47] . However, the sterically more hindered even more challenging α,α‐disubstituted systems as studied herein were not included in these investigations.…”
Section: Resultsmentioning
confidence: 97%
“…Co(acac) 2 catalyzed oxygen mediated hydration failed to deliver the desired β‐hydroxy product. Of note, Rizzacasa and co‐workers previously demonstrated aerobic hydration of α,β‐unsaturated esters by using a designed Mn‐catalyst [47] . However, the sterically more hindered even more challenging α,α‐disubstituted systems as studied herein were not included in these investigations.…”
Section: Resultsmentioning
confidence: 97%
“…In 2019, the groups of Donnelly and Rizzacasa disclosed an enhanced hydration of α,β-unsaturated esters toward αhydroxy esters (compared to the previously mentioned work by Mukaiyama et al) 88 by the use of a Mn(III) complex with a Schiff base ligand (Mn-25, Figure 14). 93 Notably, the authors reported that the more reactive silane previously used by Shenvi (Ph(iPrO)SiH 2 ) 27 did not present a significant improvement for the reaction; therefore, the reaction conditions remained similar to Mukaiyama's report. Furthermore, they also found that the treatment with P(OEt) 3 was not necessary, as previously reported by Magnus, 89 suggesting that the hydroperoxides are not formed in significant amounts or that they could be reduced in situ by the silane in excess.…”
Section: Hydroarylationmentioning
confidence: 62%
“…Of note,R izzacasa and co-workers previously demonstrated aerobic hydration of a,b-unsaturated esters by using ad esigned Mn-catalyst. [47] However, the sterically more hindered even more challenging a,adisubstituted systems as studied herein were not included in these investigations.…”
Section: Forschungsartikelmentioning
confidence: 99%